The Effects of Quantitative Easing on Bank Lending Behavior - Rodnyansky, Alexander; Darmouni, Olivier M. (Review of Financial Studies, 2017)
Banks’ exposure to large-scale asset purchases, as measured by the relative prevalence of mortgage-backed securities on their books, affects lending following unconventional monetary policy shocks. Using a difference-in-differences identification strategy, this paper finds strong effects of the first and third round of quantitative easing (QE1 and QE3) on credit. Highly affected commercial banks increase lending by 2% to 3% relative to their counterparts. QE2 had no significant impact, consistent with its exclusive focus on Treasuries sparsely held by banks. Overall, banks respond heterogeneously, and the type of asset being targeted is central to QE. Received January 13, 2016; editorial decision January 18, 2017 by Editor Philip Strahan.